Cover Picture: MOFs Extend the Lifetime of Pd(II) Catalyst for Room Temperature Alkenylation of Enamine‐Like Arenes (Adv. Synth. Catal. 20/2018). Issue 20 (4th October 2018) - Cirujano, Francisco G.; Leo, Pedro; Vercammen, Jannick; Smolders, Simon; Orcajo, Gisela; De Vos, Dirk E.
Abstract : Theinside cover picture, provided by Cirujano and co‐workers, illustrates the results of their work on recycling catalytic amounts of Pd(OAc)2 in the presence of redox active, stable and reusable metal‐organic microporous frameworks (MOF‐74), thus achieving the C−H functionalization of pharmaceutically interesting aza‐heterocycles with alkenes. This is the first time that redox/acid active sites in the porous, non‐toxic and earth abundant robust MOF‐74 platform are used to avoid the fast deactivation of the cationic Pd species during the room temperature and ambient pressure alkenylation of indoles and uracils under batch and continuous flow conditions. Details can be found in the communication on pages 3872–3876 (F. G. Cirujano, P. Leo, J. Vercammen, S. Smolders, G. Orcajo, D. E. De Vos, Adv. Synth. Catal .2018, 360, 3872–3876; DOI:10.1002/adsc.201800817 )